High diversity of fungal ecological groups in Andean–Patagonian Nothofagus forests - Max Emil Schön; Sarah Zuern; Milena Vera; Sigisfredo Garnica (PLoS ONE, 2023)
Native Andean–Patagonian Nothofagus forests harbour a unique diversity of microorganisms with diverse ecological roles. Although ectomycorrhizal associations constitute an important fragment of the biota associated with these forests, the factors affecting such communities are largely unknown. We investigated the biodiversity, relative abundance, and composition of ectomycorrhizal fungal communities in relation to two host tree species and ages and the soil properties in six monospecific and mixed evergreen–deciduous Nothofagus forests. We used the internal transcribed spacer (ITS2) region by sequencing 9,600 ectomycorrhizae (ECM) root tips for the identification of fungi. In total, 1,125 fungal taxa at the genus level distributed over 131 orders were identified. The phyla Ascomycota (34.5%) and Basidiomycota (62.1%) were the most abundant, whereas Mucoromycota (3.1%), Chytridiomycota, Cryptomycota, Olpidiomycota, and Zoopagomycota occurred less frequently. The highest taxon diversity was found in old trees, whereas young trees often exhibited a lower diversity of the associated fungi. The fungal taxa were grouped into seven broad ecological categories, of which saprotrophic associations were most common, followed by pathotrophic, pathotrophic–saprotrophic–symbiotrophic, pathotrophic–saprotrophic, and symbiotrophic associations. We did not detect significant differences in the number of taxa in each category between young and old N. dombeyi and N. obliqua. Overall, the scale of the Illumina sequencing approach allowed us to detect a fungal taxa diversity that would not be possible to find through surveys of fruiting bodies alone and that have never been observed in Nothofagus forests before. Our findings suggest the impact of the proximity between sites, the similarity of the soil conditions, and anthropogenic use of the forests on the belowground fungal community’s diversity and composition. Furthermore, there were differences between above- and belowground occurrences of the edible mushrooms B. loyo and Ramaria spp. However, future research, including on EMC tips found beneath fairy rings could provide significantly better correlations with the occurrence of aboveground fruiting body.